OARSI Clinical Trials Recommendations: Design and conduct of clinical trials of lifestyle diet and exercise interventions for osteoarthritis. Issue 5 (May 2015) - Messier, S.P.; Callahan, L.F.; Golightly, Y.M.; Keefe, F.J.
Summary: The objective was to develop a set of "best practices" for use as a primer for those interested in entering the clinical trials field for lifestyle diet and/or exercise interventions in osteoarthritis (OA), and as a set of recommendations for experienced clinical trials investigators. A subcommittee of the non-pharmacologic therapies committee of the OARSI Clinical Trials Working Group was selected by the Steering Committee to develop a set of recommended principles for non-pharmacologic diet/exercise OA randomized clinical trials. Topics were identified for inclusion by co-authors and reviewed by the subcommittee. Resources included authors' expert opinions, traditional search methods including MEDLINE (via PubMed), and previously published guidelines. Suggested steps and considerations for study methods (e.g., recruitment and enrollment of participants, study design, intervention and assessment methods) were recommended. The recommendations set forth in this paper provide a guide from which a research group can design a lifestyle diet/exercise randomized clinical trial in patients with OA.